Arytenoid cartilage dislocation mimicking bilateral vocal cord paralysis: A case report. Issue 45 (November 2017) - Chun, Eun H.; Baik, Hee J.; Chung, Rack K.; Lee, Hun J.; Shin, Kwangseob; Woo, Jae H.
Abstract: Rationale: Arytenoid dislocation is very rare and may be misdiagnosed as vocal cord paralysis or a self-limiting sore throat. Patient Concerns: A 70-year-old male (70 kg, 156 cm) was scheduled for transurethral resection of bladder tumors. A McGrath videolaryngoscope, with a basic cuffed Mallinckrodt oral tracheal tube of 7.5 mm internal diameter, was used to successfully intubate his trachea. The duration of surgery was 25 minutes. In the recovery room, he complained of sore throat and dyspnea with inspiratory stridor, which were not resolved after intravenous injection of 10 mg of dexamethasone. Diagnoses: The otolaryngological examination revealed midline fixation of the bilateral vocal folds, suggestive of bilateral arytenoid dislocation or bilateral vocal cord palsy. The latter was ruled out because there was no evidence of recurrent laryngeal nerve injury. Interventions: Under general anesthesia, a closed reduction was performed using laryngoscopic forceps to apply posterolateral pressure on the arytenoid joints on both sides. Only the dislocation of the left cricoarytenoid joint could be easily reduced, whereas reduction of the right joint was not possible. Outcomes: On postoperative day 7, examination with a rigid laryngoscope showed a medially fixed right vocal fold, with full compensation by the left vocal fold. Computed tomography of the neck showed no pathologic findings. Six weeks after surgery, the patient had regained his normal voice with no complications. Lessons: Although arytenoid dislocation is a rare complication, it should be considered even in patients with uncomplicated tracheal intubation. Early diagnosis and the optimal therapeutic approach are critical for restoration of the patient's original vocal cord function. Abstract : Supplemental Digital Content is available in the text